Establishment of the Quantitative Analysis of Multiindex in Euphorbia lathyris by the Single Marker Method for Euphorbia lathyris Based on the Quality by Design Concept - Feng Xuehua; Zhou Guangjiao; Tao Ali (Journal of Analytical Methods in Chemistry)
Methods. The influences of methanol proportion, flow rate, column temperature, and injection volume in the mobile phase on the chromatographic resolution of chromatographic peak of euphorbia factor L1 were experimentally studied via Plackett–Burman design, and the key analysis parameters were screened out; the key analysis parameters were optimized through the central composite design, and the chromatographic analysis conditions were established. Euphorbia factor L1 was taken as the internal reference to construct the relative correction factors for L3 and L4 relative to L1, and their contents were calculated, thus realizing the QAMS. Meanwhile, the euphorbia factor L3 and euphorbia factor L4 were determined using the external standard method, and the differences of values measured by the external standard method from the values predicted by the QAMS method were compared, in an effort to verify the accuracy and feasibility of the QAMS method. Results. The methanol proportion and column temperature in the mobile phase were the key analysis parameters P<0.05, and the chromatographic conditions were determined as follows. The methanol/water ratio, column temperature, detection wavelength, flow rate, and injection volume were 60 : 40, 30°C, 275 nm, 1.0 mL/min, and 10 μL, respectively. A total of 20 batches of samples were determined by the QAMS method and external standard method; the relative standard deviations (RSDs) of L3 and L4 determination results were less than 2.0%, without any significant difference. Conclusion. The QbD-based QAMS method can be used to determine the contents of euphorbia factor L3 and euphorbia factor L4 in Euphorbia lathyris L., and it is accurate and feasible.